2022
DOI: 10.3389/fpls.2022.846237
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Potential of Wheat-Pea Species Mixtures: Evaluation of Multifunctional Performance and Wheat Diversity

Abstract: Species mixtures and heterogeneous crop populations are two promising approaches for diversified ecological cropping systems with increased resilience and reduced dependency on external inputs. Inter- and intraspecific diversity were evaluated in combination using 15 wheat (Triticum aestivum) entries, including line cultivars and heterogeneous populations (HPs), from central Europe and Hungary and one winter pea cultivar under organic conditions. Monocultures and wheat mixtures were evaluated multi-functionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Furthermore, the ANOVA across cereal species and design indicated that different species have different land-use efficiency in the different design types with finger millet having higher land-use efficiency than other crops in additive designs, whereas no difference was observed between the species in replacement designs. The number of studies, which report LER from different wheat genotypes, was very limited [but see Timaeus et al (2022)]; because of the high importance of wheat for global food security, we suggest that more research is needed to investigate the performance of different wheat genotypes in intercropping. Conversely, the effect of design on land use efficiency in legumes is not significant, whereas species effect is significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ANOVA across cereal species and design indicated that different species have different land-use efficiency in the different design types with finger millet having higher land-use efficiency than other crops in additive designs, whereas no difference was observed between the species in replacement designs. The number of studies, which report LER from different wheat genotypes, was very limited [but see Timaeus et al (2022)]; because of the high importance of wheat for global food security, we suggest that more research is needed to investigate the performance of different wheat genotypes in intercropping. Conversely, the effect of design on land use efficiency in legumes is not significant, whereas species effect is significant.…”
Section: Discussionmentioning
confidence: 99%
“…In an additive design, the planting density of both species in the mixture may be equivalent or somewhat reduced compared to their sole stand resulting in planting densities leading to density equivalent ratios > 1 and up to 2. For example, pea-oat mixtures may be composed of 100% peas and 20% oats compared to the pure stand densities (Gronle et al, 2015) or wheat-winter pea mixtures of 70% wheat with 50% pea (Timaeus et al, 2022). In replacement designs, the density of one sole crop species is proportionally (based on sole crop densities) replaced by the other species resulting in a density equivalent ratio of 1.…”
Section: Evaluation Of the Performance Of Different Cereal/legume Spe...mentioning
confidence: 99%
“…The broad range of aspects of PRP of mixtures indicates that SM performance was perceived multifunctionally. This is supported by empirical multifunctional SM evaluation [6]. Farmers that work under nutrient-limited conditions, especially in organic farming, focus on nutrient cycling and enhancing biological nitrogen fixation.…”
Section: Conditions For Relative Mixture Advantages and Economic Chal...mentioning
confidence: 95%
“…A prime example are wheat pea mixtures that are rarely used in practice [9] despite their manifold advantages, such as increased protein content in wheat and an additional yield of peas [6]. The usually discussed conundrum is the separation of baking wheat from mixtures.…”
Section: Moving Beyond Current Practice: Farm and Food System Level I...mentioning
confidence: 99%
See 1 more Smart Citation